Computational Investigations of Arylnaphthalene Lignan Lactones as Anticancer Agents - Rachida Mansouri; Abdeslem Bouzina; Yousra Ouafa Bouone (Chemistry Proceedings, 2024)
Cancer is a significant global health challenge, comprising over 200 distinct types that severely impact life expectancy and account for high mortality rates in the 21st century. This complexity underscores the urgent need for ongoing research, preventive strategies, and improved treatment options. In the quest for new anticancer drug candidates, arylnaphthalene lignan lactones—natural compounds found in plants like Phyllanthus and Cleistanthus—have gained attention due to their antioxidant, anti-inflammatory, and anticancer properties. An in silico study was conducted to evaluate their potential against colon cancer by targeting epidermal growth factor receptor (EGFR), a key tyrosine kinase. Docking simulations revealed that these compounds exhibited excellent stability within the active site of EGFR, with docking scores of −8.02 and −7.96 kcal/mol. Further, the derivatives demonstrated significant interactions, including hydrogen bonds with Met 769 and hydrophobic contacts within the EGFR cavity, akin to those formed by the known inhibitor 4-anilinoquinazoline. An ADMET analysis was also performed to evaluate their pharmacokinetic properties and toxicity, further supporting their potential as promising anticancer agents.